Examination of the Validity of Skin Ultrasound to Quantitate Skin Involvement for Multicenter Clinical Trials in Patients with Systemic Sclerosis (SSc): A Systematic Literature Review (SLR) - Aly, Omar M.; Kafaja, Kevin L.; Suliman, Yossra A.; Furst, Daniel E. (ACR open rheumatology, 2022)
Objective The study objective was to conduct a systematic literature review (SLR) of ultrasound of the skin in patients with systemic sclerosis (SSc) to establish the degree to which ultrasound of the skin has been validated, using the Outcome Measures in Rheumatology (OMERACT) Filter. Methods We conducted an SLR of publications between 1950 and 2018, using PubMed and Cochrane library, to examine ultrasound validity to quantitate SSc skin involvement. Inclusion criteria were as follows: (1) in English; (2) used the 1980 or 2013 classification criteria for SSc criteria; (3) either a randomized controlled trial, an observational study, or a case study including more than 15 patients; (4) subjects 18 years of age or older; (5) for mixed patient populations, SSc results were separable; and (6) the ultrasound machine was clearly described. Exclusion criteria were as follows: (1) not in English; (2) data did not record at least one of the validation criteria; (3) subjects aged less than 18 years; (4) subjects had disease other than SSc (eg, localized scleroderma or scleroderma‐like disease); (5) a letter to the editor or an editorial; and (6) involved a modified Rodnan skin score of less than 2. Descriptive statistics were generated for each criterion. Results From an initial 292 citations, 14 articles (1,055 patients) met inclusion and exclusion criteria. The status of validation for ultrasound was evaluated by using the OMERACT criteria of truth, discrimination, and feasibility (in turn divided into nine different criteria). Face, criterion, content, construct, reliability, and responsiveness criteria were met, and the feasibility criterion was partially met, whereas discrimination and reproducibility criteria were not met. Conclusion Based on an SLR through December 31, 2018, ultrasound of the skin met some but not all validation criteria for use in clinical trials.